Minority carrier diffusion length in AlxGa1‐xN (x = 0.1) grown by ammonia molecular beam epitaxy. Issue 4 (30th March 2015) - Malin, Timur; Gilinsky, Alexander; Mansurov, Vladimir; Protasov, Dmitriy; Yakimov, Eugeny; Zhuravlev, Konstantin
Abstract: The room‐temperature minority carrier diffusion length in n ‐Al0.1 Ga0.9 N grown by ammonia molecular beam epitaxy on (0001) sapphire for photodetector applications has been investigated. The measurements were performed using the spectral dependence of the photocurrent detected by the built‐in p‐n ‐junction on thinner layer samples, and by the electron beam induced current technique on films of up to 2 µm in thickness. The results show that the hole diffusion length in n ‐AlGaN films amounts to 120‐150 nm, which is by 3‐4 times larger than that in GaN films grown under similar growth conditions. The thicker films do not show a considerable improvement in the hole diffusion length value. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)